1962
DOI: 10.1152/jappl.1962.17.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical function of the main pulmonary artery

Abstract: The relationship among the longitudinal strain, circumferential strain, lateral intravascular pressure, blood flow, and longitudinal motion was examined in the main pulmonary artery of living, open-chested dogs. Results indicate: 1) The mean value for longitudinal extensibility was 0.73% change in length per centimeter of water pressure (± .19 sd ± .04 sem). 2) The mean value for volume distensibility was 2.28% change in volume per centimeter of water pressure (± .9 sd ± .17 sem). 3) The magnitude of the radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1968
1968
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Since the whole pulmonary arterial system has a compliance of ,4 mL?mmHg -1 (table 1), a large part of arterial compliance is located in the periphery. This estimate is in line with earlier publications showing that a considerable proportion of the pulmonary arterial compliance is distal to the proximal large arteries [30,[40][41][42][43][44][45][46]. Thus, with an embolus (large) part of peripheral arteries is lost meaning that their compliance is lost resulting in a decrease of the total compliance, and by the loss of vessels the resistance is increased.…”
Section: Why the Product Of Resistance And Compliance Is Constantsupporting
confidence: 91%
“…Since the whole pulmonary arterial system has a compliance of ,4 mL?mmHg -1 (table 1), a large part of arterial compliance is located in the periphery. This estimate is in line with earlier publications showing that a considerable proportion of the pulmonary arterial compliance is distal to the proximal large arteries [30,[40][41][42][43][44][45][46]. Thus, with an embolus (large) part of peripheral arteries is lost meaning that their compliance is lost resulting in a decrease of the total compliance, and by the loss of vessels the resistance is increased.…”
Section: Why the Product Of Resistance And Compliance Is Constantsupporting
confidence: 91%
“…Increased wall stiffness in established pulmonary hypertension has been reported by several authors (Milnor et al, 1969;Patel et al, 1962;Elkins et al, 1974;Caro and Harrison, 1962). Milnor et al (1969) reported impedance data on seven patients with mitral valve disease and pulmonary hypertension showing higher Z o and C o with progressive elevations of pulmonary artery pressures; all of these patients had elevated left atrial pressures and normal or decreased blood flows.…”
Section: Pulmonary Hypertension and Chronic High-flow Stressmentioning
confidence: 71%
“…It is well accepted that significant vasomotor activity exists in small precapillary resistance ves- sels; however, there also is evidence of changes in mechanical properties of the larger pulmonary arteries under physiological stress and adrenergic stimulation (Ingram et al, 1968). Patel et al (1962) showed that the main pulmonary artery has huge volume distensibility. It has been demonstrated that the dynamic transmission characteristics of the proximal vessels have a contributory role in the control of regional pulmonary flow patterns (Maloney et al, 1968).…”
Section: Resistance and Impedancementioning
confidence: 99%
“…Although smooth muscle fibers cannot be regarded as perfect elastic structures, the net behavior of major pulmonary arterial walls up to transmural pressures of approximately 40 mm Hg is that of a perfect elastic structure (19). It seems reasonable to conclude that the acute reversible changes in volume-distensibility characteristics of pulmonary vessels during the brief changes in pump rate would be due to changes in smooth muscle behavior.…”
Section: Effect Of Sympathetic Nerve Stimulation In Adjusting Vascularmentioning
confidence: 99%